2021
DOI: 10.3389/fonc.2021.595609
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CHST15 Sponges miR-155-5p and miR-194-5p to Promote the Immune Escape of Lung Cancer Cells Mediated by PD-L1

Abstract: BackgroundThe effects of up-regulated CircCHST15 on lung cancer remained unclear. In this study, the role of CircCHST15 in lung cancer was investigated.MethodsDual-luciferase reporter verified the bioinformatics prediction that CircCHST15 targeted miR-155-5p and miR-194-5p. The correlation between CircCHST15 and PD-L1 was analyzed by Pearson analysis. CCK-8 and colony formation was performed to determine the viability and proliferation of lung cancer cells. After the lung cancer (subcutaneous-xenotransplant) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
(57 reference statements)
1
27
0
Order By: Relevance
“…Previous studies have shown that miRNA is abnormally expressed in follicular fluid and has been shown to modulate follicular development in human GCs. miR-194 has been implicated in several different malignancies, such as gastric cancer cell growth and lung cancer cell apoptosis [ 38 , 39 ]. however, the role and effect of miR-194 in ovarian GCs are not entirely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miRNA is abnormally expressed in follicular fluid and has been shown to modulate follicular development in human GCs. miR-194 has been implicated in several different malignancies, such as gastric cancer cell growth and lung cancer cell apoptosis [ 38 , 39 ]. however, the role and effect of miR-194 in ovarian GCs are not entirely understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, circCHST15 induces the production of both protumoral (TNF-β, and IL-10 and PD-L1) and antitumoral cytokines (IFN-γ and CCL17). The authors propose that increased expression of PD-L1 induces the inactivation CD8 + cells, leading to immune escape in lung cancer (Yang et al, 2021). In lung adenocarcinoma, circRNA-002178 increases PD-L1 expression, by acting as sponge of miR-34.…”
Section: Regulation Of Circrnas-mirnas-mrnas Modulating the Response ...mentioning
confidence: 99%
“…Multiple studies have demonstrated the role of circRNAs in regulating the expression of PD-L1 through the circRNA–miRNA–mRNA axis. CircCHST15 facilitated the PD-L1-mediated immune escape of lung cancer cells by inhibiting miR-155-5p and miR-194-5p [ 19 ]. The circ-CPA4–let-7 miRNA–PD-L1 axis regulated the growth of NSCLC cells and inhibited cytotoxic T cells in TIME [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported the role of circRNAs in regulating the expression of PD-L1 through circRNA–miRNA–mRNA axis. A number of circRNAs, such as circBART2.2, hsa_circ_0136666, circ-keratin 6c, CDR1-AS, circ-VIM, hsa_circ_0003288, CircCHST15, circ-CPA4, hsa-circRNA-002178, and Circ_0000284 were shown to affect PD-L1 expression, leading to tumor immune escape in various types of cancers, including nasopharyngeal carcinoma, colorectal cancer, esophageal cancer, hepatocellular carcinomas (HCC), and lung cancer [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Our previous study discovered the correlation between hsa_circ_0000190 plasma level and PD-L1 level in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%